The Plasmodium vivax merozoite surface protein 3β sequence reveals contrasting parasite populations in southern and northwestern Thailand. - Chaturong Putaporntip; Jun Miao; Napaporn Kuamsab; Jetsumon Sattabongkot; Jeeraphat Sirichaisinthop; Somchai Jongwutiwes; Liwang Cui (Public Library of Science (PLoS), 2014)
Malaria control efforts have a significant impact on the epidemiology and parasite population dynamics. In countries aiming for malaria elimination, malaria transmission may be restricted to limited transmission hot spots, where parasite populations may be isolated from each other and experience different selection forces. Here we aim to examine the Plasmodium vivax population divergence in geographically isolated transmission zones in Thailand.We employed the P. vivax merozoite surface protein 3β (PvMSP3β) as a molecular marker for characterizing P. vivax populations based on the extensive diversity of this gene in Southeast Asian parasite populations. To examine two parasite populations with different transmission levels in Thailand, we obtained 45 P. vivax isolates from Tak Province, northwestern Thailand, where the annual parasite incidence (API) was more than 2%, and 28 isolates from Yala and Narathiwat Provinces, southern Thailand, where the API was less than 0.02%. We sequenced the PvMSP3β gene and examined its genetic diversity and molecular evolution between the parasite populations.Of 58 isolates containing single PvMSP3β alleles, 31 sequence types were identified. The overall haplotype diversity was 0.77 ± 0.06 and nucleotide diversity 0.0877±0.0054. The northwestern vivax malaria population exhibited extensive haplotype diversity (HD) of PvMSP3β (HD=1.0). In contrast, the southern parasite population displayed a single PvMSP3β allele (HD=0), suggesting a clonal population expansion. This result revealed that the extent of allelic diversity in P. vivax populations in Thailand varies among endemic areas.Malaria parasite populations in a given region may vary significantly in genetic diversity, which may be the result of control and influenced by the magnitude of malaria transmission intensity. This is an issue that should be taken into account for the implementation of P. vivax control measures such as drug policy and vaccine development.